Genotoxic effect of ranitidine on the DNA of polychromatic erythrocytes of Rattus norvegicus strain Holtzman - Quiñones-Cerna, María Elvira (2022)
Background: Ranitidine is a drug that is associated with mutagenesis by generating genetic alterations and / or cell carcinogenesis, but its genotoxicity in polychromatic erythrocytes is unknown. Therefore, the effect of ranitidine on DNA of micronucleated polychromatic erythrocytes (EPC) in albino rats (Rattus norvegicus, Holtzman strain) was researched by the micronucleus test. Materials and methods: Four groups of rats were studied: negative control with physiological saline solution (0.5 ml for 15 days); positive control with cyclophosphamide (dose 50 mg / kg for 2 days) and two experimental groups treated with ranitidine (doses 2 and 4 mg / kg for 15 days). The rats were euthanized and cytological preparations were obtained by 30 min staining in 5% giemsa. Results: An increase in the size and significant increase in the number of micronuclei in the EPC was found in the experimental groups of 285.27 ± 10.25, compared to the negative control of 70.38 ± 6.47. The genotoxicity index was three times higher in the experimental groups (12.10 ± 0.49; 2 mg / kg NRT and 14.26 ± 0.51; 2 mg / kg NRT) in relation to the negative control (3.52 ± 0 , 32). Conclusions: Ranitidine generates an increasing stimulus of the genotoxic index with a high frequency of micronuclei in EPC of R. norvegicus strain Holtzman.